THE EFFECT OF LEMON JUICE (Citrus limon) IN LIVER HISTOPATHOLOGIC APPEARANCE OF MALE MICE (Mus musculus L.) EXPOSED BY MONOSODIUM GLUTAMATE (MSG) - Aji, Dela Destiani; Mulyaningsih, Ruri Eka Maryam; MZZ, Ahmad Fariz (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Excessive consumption of MSG can cause the formation of free radicals in the body. Continuous use of MSG will cause free radical accumulation and oxidative stress in the liver. An antioxidant is one of the substances that has an ability to eliminate free radicals and protect the liver from oxidative stress. Lemon is a fruit that has benefits as a natural antioxidant. This study aims to determine the effect of administering lemon juice on the histopathological appearance of the liver exposed by MSG.Methodology: This post-test only control group design experimental study used 30 male white mice which were randomly divided into five groups: NC group, C(-) group, D1 group, D2 group, and D3 group. After 7 days of adaptation and randomized grouping, the mice were treated differently based on their group. All groups, except the NC group, were exposed to 4mg/gBW dose of MSG orally for 14 days. On the 15th day, MSG exposure was stopped and after that D1 group, D2 group, and D3 group were given lemon juice with a dose of each group 3.33ml/kgBW, 6.67 ml/kgBW, 13.33 ml/kgBW. The lemon juice was given once a day for 14 days using the gastric sonde. Histopathology examination was analyzed by pathologist in Gunung Jati Hospital, Cirebon, IndonesiaResults: Significant differences of liver histopathology were obtained between the normal control group with the dose 3 group (p = 0.005), the normal control group with the dose 2 group (p = 0.019), the normal control group with the dose group (p = 0.019) and between the negative control groups with dose 3 group (p = 0.027). Dose 3 group has higher liver damage compared to a normal control group and negative control group characterized by the form of parenchymatous degeneration. Conclusion: Lemon juice has a negative effect on the histopathology appearance of male white mice?s (Mus musculus L.) liver exposed by monosodium glutamate (MSG). Further studies are needed to validate the effect of the active compound and toxicity of lemon juice and to reveal the precise mechanisms on how lemon juice affects the hepatocytes.